Eksistensi Industri Anyaman Bambu Di Era Modernisasi Ditinjau Dari Segi Desain Dan Teknik Finishing Di Sanggar Kreatif “Bunga Matahari” Binjai - Safira Santoso; Mesra Mesra; Dwi Budi Wiwaramulja (Mahesa Research Center, 2021)
This study aims to: determine the existence of woven bamboo, survival strategies, materials in the finishing process of woven bamboo products at Sunflower Studio. The population in this study were 200 pieces of woven bamboo in the Sunflower Studio. The samples used were 20 products from 10 types of products produced. The method used is descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of this study indicate that the sunflower weaving business still exists because it is supported by maintaining the quality of materials and after-service to consumers. Sanggar Bunga Matahari can maintain a neat and symmetrical product design, so that consumers are interested in continuing to order their products. The finishing technique applied by the Sunflower Studio is H2O immersion, staining and followed by varnish.